The case for an autoimmune aetiology of type 1 diabetes. (21st October 2015) - Mannering, S. I.; Pathiraja, V.; Kay, T. W. H.
Summary: Type 1 diabetes (T1D) develops when there are insufficient insulin‐producing beta cells to maintain glucose homeostasis. The prevailing view has been that T1D is caused by immune‐mediated destruction of the pancreatic beta cells. However, several recent papers have challenged the long‐standing paradigm describing T1D as a tissue‐specific autoimmune disease. These authors have highlighted the gaps in our knowledge and understanding of the aetiology of T1D in humans. Here we review the evidence and argue the case for the autoimmune basis of human T1D. In particular, recent analysis of human islet‐infiltrating T cells brings important new evidence to this question. Further data in support of the autoimmune basis of T1D from many fields, including genetics, experimental therapies and immunology, is discussed. Finally, we highlight some of the persistent questions relating to the pathogenesis of human type 1 diabetes that remain to be answered.